2015
DOI: 10.1596/1813-9450-7362
|View full text |Cite
|
Sign up to set email alerts
|

Improving Education Outcomes in South Asia: Findings from a Decade of Impact Evaluations

Abstract: There have been many initiatives to improve education outcomes in South Asia. Still, outcomes remain stubbornly resistant to improvements, at least when considered across the region. To collect and synthesize the insights about what actually works to improve learning and other education outcomes, this paper conducts a systematic review and metaanalysis of 29 education-focused impact evaluations from South Asia, establishing a standard that includes randomized control trials and quasi-experimental designs. It f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…For example, in romania, it is quite common for children to attend school for only half the day as part of a two-shift system . In South Asia, despite figures indicating very positive increases in enrollment rates and gender parity among students (as indicated by the Un statistics), academic outcomes are still poor throughout the region (Asim et al 2015). It would seem that a major reason for this is the short length of the school day in some countries in the region such as India where the school day typically lasts for only three hours compared to six to eight hours per day on average in oECD countries (Banerjee and Duflo 2011).…”
Section: Learning Spaces and Educational Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in romania, it is quite common for children to attend school for only half the day as part of a two-shift system . In South Asia, despite figures indicating very positive increases in enrollment rates and gender parity among students (as indicated by the Un statistics), academic outcomes are still poor throughout the region (Asim et al 2015). It would seem that a major reason for this is the short length of the school day in some countries in the region such as India where the school day typically lasts for only three hours compared to six to eight hours per day on average in oECD countries (Banerjee and Duflo 2011).…”
Section: Learning Spaces and Educational Technologymentioning
confidence: 99%
“…There is robust evidence, for example in South Asia, that "school building programs rank among the most effective educational interventions." (Asim et al 2015;Petrosino et al 2012) According to the Center for Public Education, (Center for Public Education 2016) equity is achieved in education when all students receive the resources that they need to graduate fully equipped to succeed after high school. Whether the goal is high school graduation, university success, or just to finish elementary school, policymakers aim to ensure an equal and fair distribution of the resources that students need to achieve their goals, including adequate school facilities, so that every member of each age group has the opportunity to attend school.…”
Section: Implications For Equitymentioning
confidence: 99%
“…We include both published and unpublished reviews, but include only reviews of interventions in developing countries that were either published or posted online (in the case of unpublished work) in 2013 or 2014 in order to maximize the probability that the reviews draw on a similar underlying population of education studies. Reviews of learning interventions in developing countries continue to be written since this time window, including Asim et al (2015), Masino and Niño-Zaraz ua (2015), Glewwe and Muralidharan (2015), and Snilstveit et al (2015).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The results have depended on inputs, outputs and the choice of measurement. Asim et al (2015) provides a systematic framework of available innovations in education, which consists of three dimensions. The first dimension is the supply versus demand side.…”
Section: Impact Evaluation In Educationmentioning
confidence: 99%
“…has been a lot of impact evaluation research concerning interventions in education. The reviews can be found in the studies from i.e Glewwe and Muralidharan (2015),Evans and Popova (2015),Conn (2014),Glewwe et al (2013),Kremer et al (2013),Krishnaratne et al (2013),Masino and Niño-Zarazúa (2015),McEwan (2015),Asim et al (2015),. andMurname and Ganimian (2014).…”
mentioning
confidence: 99%